Genetic Comparison of Human Parainfluenza Virus Type 3 Detected in Respiratory Samples from Patients with Encephalopathy and Airway Inflammation in Aichi Prefecture, Japan - Adachi, Hirokazu; Minagawa, Hiroko; Hirose, Emi; Nakamura, Noriko; Niimi, Hitomi; Saito, Noriko; Ito, Miyabi; Sato, Katsuhiko; Yasui, Yoshihiro (Japanese Journal of Infectious Diseases, 2024)
Human parainfluenza virus type 3 (HPIV-3, human respirovirus 3) is the second most frequently detected virus in lower respiratory tract infections in children after human respiratory syncytial virus (HRSV). HPIV-3, similar to related respiratory viruses such as HRSV and influenza virus, may cause encephalopathy; however, the relevance of HPIV-3 as a pathogenic factor in encephalopathy is unknown. We attempted to detect HPIV-1, HPIV-2, HPIV-3, HPIV-4, HRSV, and human metapneumovirus (HMPV) in 136 patients with encephalitis/encephalopathy or suspected encephalitis/encephalopathy during a 6-year period from 2014 to 2019. HPIV-3 was detected in 6 patients, followed by HRSV in 3 patients. The HPIV-3 strains detected were closely related to those detected in a patient with respiratory disease during the same period. Although HPIV-3 is less widely recognized than HRSV as a triggering virus of encephalopathy, our results suggest that HPIV-3 is as important as HRSV. Surveillance of the causative viruses of encephalopathy, including HPIV-3, would help clarify the causes of encephalopathy in Japan, as the cause is currently reported in less than half of cases in Japan.